Development of technology for recycling the liquid iron-containing wastes of steel surface etching - Yatskov, Mykola; Korchyk, Natalia; Budenkova, Nadia; Kyrylyuk, Svitlana; Prorok, Oleg (Eastern-European Journal of Enterprise Technologies, 2017)
Results of the conducted theoretical and practical research into processes of recycling the iron-containing wastes of steel surfaces etching are presented, namely, regeneration and utilization of used-up etching solutions and purification of wash water. Based on the results of research, new technological approaches to waste recycling with the view of minimizing their discharge into the environment and reducing costs of an enterprise were substantiated and practically tested. The existing technologies for recycling the iron-containing wastes of steel surfaces etching require updating in order to minimize their discharge into environment and to reduce the expenditures of an enterprise. It is known that in the theoretical approach to the concentrated solutions of electrolytes, so many correction coefficients were introduced to the theory of calculations that the results of calculations lose their physical essence. Therefore, for the concentrated solutions, it is necessary to determine the basic parameters experimentally. After exploring the technology of wash water purification, it was established that the most effective way is treatment with lime with flocculant (brand Zetag 8180) and filtering through a filter with polystyrene foam. A part of the treated water was passed through a reverse osmosis system, which, at subsequent mixing with the main part of the flow, makes it possible to obtain water of the “Technical water” category II quality. In order to develop a technology for the regeneration of used-up etching solutions, we conducted research into redox properties of UES both with Н2О2 and without it at different pH values. The optimal scheme of treatment is the one that includes alkalization with a 40 % solution of Са(ОН)2 until achieving pH=4.2, and treatment with a hydrogen peroxide solution. The technology of recycling of used-up etching solutions with the application of UES as a chemical reagent makes it possible: 1) with the alkalization, to provide optimal extraction of zinc from complex compounds, which also increases at a co-sedimentation of zinc and iron; 2) to provide optimal conditions for the oxidation of organic compounds in alkaline wastewater after degreasing operations.